Origen's parallel bible: textual criticism, apologetics, or exegesis? - Law, T (Oxford University Press, 2008)
The assumption held by most Septuagint scholars that Origen compiled the Hexapla for a text-critical or apologetic use is challenged. A third possibility - that Origen's motivations were more exegetical - is considered. This third view has not received the attention it deserves, even though it has been raised several times in the past few decades. Here I examine Origen's life and thought with particular attention to his approach to and use of Scripture. After discussing the content and structure of the Hexapla, I evaluate the two theories that are most often used to explain the genesis of the Hexapla, and attempt to show their insufficiency alone to account for Origen's work. The third proposal is then tested to see if an exegetical motivation fits more harmoniously with Origen's attitude towards Scripture.